(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Road accidents are random or accidental incidents that are subject to intermittent distributions ,the most important distributions are (binomial distribution , Poisson distribution , negative binomial distribution) , these incidents are categorical according to the nature of the accident (fatal, fatalwith wounded , wounded only), in this research , we considered the impact of the type of accident (collision , overturned , run over ) and the scene (inside the city , outside the city ) and it,s impact on the nature of the incident individually on the one hand and on the other hand using the contingency tables of class (r×c×k) and estimate the logarithmic model for each case and selecting the optimal model by adopting the maximum likelihood ratio using road accident data in the holy province of Karbala .